What methods are effective to reduce operative interventions and maternal morbidity in women during the second stage of labor?. Issue 1 (January 2018) - Lauters, Rebecca; Odom, Michael
Abstract : EVIDENCE‐BASED ANSWER : Delayed pushing decreases the risk of operative vaginal delivery by 23% and time spent pushing by 11 minutes in nulliparous women with epidural anesthesia (SOR: A, meta‐analysis of RCTs). Forceps use leads to 35% fewer failed vaginal deliveries compared with vacuum but increases maternal morbidity (third/fourth degree lacerations, vaginal trauma, flatus incontinence) (SOR: A, meta‐analysis of RCTs). Use of a dental support device may reduce the rate of operative vaginal delivery and Cesarean delivery in nulliparous women without altering the duration of second‐stage labor (SOR: C, single small RCT).